Shame and Secrecy of Do Not Resuscitate Orders: An Historical Review and Suggestions for the Future - O’Connor, John (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2021)
This paper clarifies some of the longstanding difficulties in negotiating Do Not Resuscitate Orders by reframing the source of the dilemmas as not residing with either the patient or the physician but with their relationship. The recommendations are low cost and low-tech ways of making major improvements to the care and quality of life of the most ill patients in hospital. With impending physician-assisted death legislation there is an urgency to find more efficient and beneficial ways for clinicians and patients to address resuscitation issues at the bedside. Paradigmatic shifts in the nature of the patient-physician relationship will need to be encouraged by the larger community. These encouraged shifts address the concepts of passive/inferior patient – active/superior physician, patient ownership of and access to all their health care information, and treating the patient as a major participant in the delivery of health care. These recommended changes will not in themselves make any patient, physician or other healthcare provider more humane and open in the patient’s final days. The goal, instead, is to have changes to the context of the discussion provide an encouraging environment for more open communication and a balanced relationship among participants with the patient being the most important.